2020
DOI: 10.3389/fnbeh.2019.00289
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Exercise vs. More Sedentary Reinforcers: Validation of an Animal Model of Tetrabenazine-Induced Anergia

Abstract: Physical activities can have intrinsic motivational or reinforcing properties. The choice to engage in voluntary physical activity is undertaken in relation to the selection of other alternatives, such as sedentary behaviors, drugs, or food intake. The mesolimbic dopamine (DA) system plays a critical role in behavioral activation or exertion of effort, and DA antagonism or depletion induces anergia in effort-based decision-making tasks. However, little is known about the neural mechanisms underlying the decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 77 publications
5
36
3
Order By: Relevance
“…These results obtained from animal studies are consistent with clinical data showing a reduced selection of high effort alternatives in depressed people tested on tasks of effort-based choice (Treadway et al, 2012;Chong et al, 2016). Administration of the vesicular monoamine transporter (VMAT-2) inhibitor tetrabenazine (TBZ), which blocks the monoamine storage and leads to a striatal DA depletion at low doses in primates (Pettibone et al, 1984), rats (Nunes et al, 2013;Podurgiel et al, 2015Podurgiel et al, , 2016Yohn et al, 2015b), and mice (López-Cruz et al, 2018;Carratalá-Ros et al, 2020) has been used to induce effort-related motivational impairments in rodents (Nunes et al, 2014;Yohn et al, 2015bYohn et al, , 2016bCorrea et al, 2018;López-Cruz et al, 2018;Rotolo et al, 2019;Carratalá-Ros et al, 2020). This drug is used in the treatment of Huntington's disease and has been reported to produce depressive symptoms including fatigue in people (Frank, 2009;Guay, 2010).…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…These results obtained from animal studies are consistent with clinical data showing a reduced selection of high effort alternatives in depressed people tested on tasks of effort-based choice (Treadway et al, 2012;Chong et al, 2016). Administration of the vesicular monoamine transporter (VMAT-2) inhibitor tetrabenazine (TBZ), which blocks the monoamine storage and leads to a striatal DA depletion at low doses in primates (Pettibone et al, 1984), rats (Nunes et al, 2013;Podurgiel et al, 2015Podurgiel et al, , 2016Yohn et al, 2015b), and mice (López-Cruz et al, 2018;Carratalá-Ros et al, 2020) has been used to induce effort-related motivational impairments in rodents (Nunes et al, 2014;Yohn et al, 2015bYohn et al, , 2016bCorrea et al, 2018;López-Cruz et al, 2018;Rotolo et al, 2019;Carratalá-Ros et al, 2020). This drug is used in the treatment of Huntington's disease and has been reported to produce depressive symptoms including fatigue in people (Frank, 2009;Guay, 2010).…”
Section: Introductionsupporting
confidence: 77%
“…This drug is used in the treatment of Huntington's disease and has been reported to produce depressive symptoms including fatigue in people (Frank, 2009;Guay, 2010). Recently, we have also demonstrated that TBZ induces depressive symptoms in the forced swim test (FST); mice show less vigorous scaping behaviors and increase immobility (Carratalá-Ros et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the neurofunctional level, administration of methylphenidate (a drug used to manage symptoms of ADHD with dual action on dopamine and norepinephrine pathways) increased neural activation in brain regions supporting response inhibition (cingulate gyrus, medial frontal gyrus, temporal and frontal gyri; Kasparbauer et al, 2015). These findings suggest that modulation of the DA2 receptor activity may have a shared influence over the preference for sedentary activity (Carratalá-Ros et al, 2020;Correa et al, 2020;López-Cruz et al, 2018) and impulsivity (Costa et al, 2013;Kasparbauer et al, 2015;Nandam et al, 2013;Weber et al, 2016). However, the role of sedentary behavior in the regulation of dopamine availability in humans remains unexplored.…”
Section: Sedentary Time and Response Inhibition-suggested Mechanismsmentioning
confidence: 99%